Challenges in Implementing the Teachers Code of Ethics in Responding to Social Dynamics - Riza Ummaroch; Sinta Devi Prastika Putri; Erna Yayuk (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2026)
This study aims to examine the various barriers faced by educators in implementing professional codes of ethics amid disruptive social transformation. Using a qualitative descriptive approach, the research analyzes how shifting social norms and the rapid penetration of digital technology have reshaped traditional ethical boundaries between teachers and students. These changes create new spaces of interaction that often blur the limits of professionalism. The findings reveal that teachers’ professional integrity is currently influenced by three main factors: the strong presence of digital environments beyond the classroom, inconsistent public expectations, and gaps in educators’ regulatory literacy. A lack of preparedness in responding to these dynamics can lead to ethical dilemmas that risk undermining the dignity of the teaching profession. Therefore, this study argues that partial or one-dimensional solutions are no longer sufficient. Systemic efforts are needed through the strengthening of contextual ethical literacy and protective institutional support. Such synergy is essential to ensure that educators possess not only intellectual competence but also adaptive moral resilience, enabling them to sustain their role as role models in an increasingly complex and dynamic educational environment.